Boom,Baby,Boom Boom - Mahy, Margaret (Great Britian Frances Lincoln Children's Books, 1997)
When Mama tells Baby that she's made a lovely lunch for him, she doesn't know that the animals are listening at the window. And they are much hungrier than Baby. While Mama bangs on her drums - boom-biddy-boom-biddy-boom-boom-boom - the yellow cat, the brown dog, the red rooster, the black-faced sheep and the brown-and-white cow each eats a titbit thrown on the floor by Baby. Good Baby gets a banana for pudding and, this time, he eats it all up. Boom-biddy-boom-biddy-yum-yum-yum!